Practical algebra : a self-teaching guide - Wong, Bobson, 1971-; Bukalov, Larisa, 1973-; Slavin, Steve, 1939- (Wiley self-teaching guides., 2022)
"This book will provide practical methods for learning Algebra. It will emphasize conceptual understanding that will allow students to make connections to what they learned before and what they will learn in the future. It will present Algebra as a logical and consistent system of ideas so that students can not only succeed in math but also gain a greater appreciation of it. This book will provide practical strategies for learning Algebra. The authors will use their teaching expertise to identify and discuss math topics currently taught in schools. We will not only offer straightforward techniques but also provide background information and explain why these techniques work. By promoting conceptual understanding, we will build readers' confidence to do math."--